APLIKASI AUGMENTED REALITY UNTUK PEMASARAN PRODUK BAKERY MENGGUNAKAN METODE MARKERLESS BERBASIS ANDROID - Haryati, Elis; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2021)
Augmented Reality technology contributes mainly to the field of marketing. Being a digital technology that can be used for marketing with the concept of a realworld object designed in 3D then displayed virtually through a smartphone screen so that it can be seen as if there was an original object being seen. Carrrefour Kepri Mall is a modern retail company, as a shopping destination, stay and play with a lifestyle concept, affordable and complete. However, the concept of a company with an unbalanced company work system. It can be seen that the marketing process that occurs in the field is still carried out using manual brochures which only include the name and price. Judging from the company's concept so that Augmented Reality technology becomes relevant to be applied to the company's work system. It is hoped that in the future by applying Augmented Reality technology the marketing process can be more effective because it is not direct and consumers can directly see existing products in 3D without having to see the product directly.